How maps and globes help us - Hackler, David; Tanis, William (Westchester : Benefic Press, 1970)
Describes the making of maps and globes and how they represent the size and shape of land and water areas.
Keywords: Globes; Globes -- Juvenile literature; Maps; Maps -- Juvenile literature